Ancient DNA reveals admixture history and endogamy in the prehistoric Aegean - Skourtanioti, Eirini; Ringbauer, Harald; Gnecchi Ruscone, Guido Alberto; Bianco, Raffaela Angelina; Burri, Marta; Freund, Cäcilia; Furtwängler, Anja; Gomes Martins, Nuno Filipe; Knolle, Florian; Neumann, Gunnar U.; Tiliakou, Anthi; Agelarakis, Anagnostis; et al. (Nature ecology & evolution, 2023)
The Neolithic and Bronze Ages were highly transformative periods for the genetic history of Europe but for the Aegean—a region fundamental to Europe’s prehistory—the biological dimensions of cultural transitions have been elucidated only to a limited extent so far. We have analysed newly generated genome-wide data from 102 ancient individuals from Crete, the Greek mainland and the Aegean Islands, spanning from the Neolithic to the Iron Age. We found that the early farmers from Crete shared the same ancestry as other contemporaneous Neolithic Aegeans. In contrast, the end of the Neolithic period and the following Early Bronze Age were marked by ‘eastern’ gene flow, which was predominantly of Anatolian origin in Crete. Confirming previous findings for additional Central/Eastern European ancestry in the Greek mainland by the Middle Bronze Age, we additionally show that such genetic signatures appeared in Crete gradually from the seventeenth to twelfth centuries bc, a period when the influence of the mainland over the island intensified. Biological and cultural connectedness within the Aegean is also supported by the finding of consanguineous endogamy practiced at high frequencies, unprecedented in the global ancient DNA record. Our results highlight the potential of archaeogenomic approaches in the Aegean for unravelling the interplay of genetic admixture, marital and other cultural practices.
Online veröffentlicht: 16. Januar 2023
Gesehen am 07.08.2024